THE ECONOMIC AND SOCIAL THOUGHT OF RODRIGO FACIO - Vega Carballo, José Luis (2013)
This article includes the main contributions of this landmark figure of social reformism of the forties and fifties of the last century, as well as very relevant sociopolitical aspects of his work and his actions, especially in the political area and the development of strategic thinking in economic and democratic planning. It emphasizes the importance of Facio as contributor, perhaps a pioneer in our country and beyond, in terms of what would later be called the theory of dependency. Finally, it calls to retake the lead of Facio on the problematic of national independence and development, in times where the advance of neoliberalism seems to have closed the routes to both.